ANALISIS HUBUNGAN ANTARA KESEIMBANGAN DAN POWER OTOT TUNGKAI PADA TENDANGAN DOLLYO CHAGI TAEKWONDO DI KABUPATEN SEMARANG - Muhammad Bagus Andrieana; Sugiharto . (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2022)
This study aims to examine the relationship between balance and leg muscle power of taekwondo athletes in Semarang Regency who attended in Ambarawa training center. Even in the training center, many athletes are still weak when kicking dollyo chagi. This study is a correlational study. The sample that researchers used is 20 athletes. The researchers used data collection techniques by conducting tests and measurements. Also, the researchers used correlational data analysis on this study. Based on the research conducted, the results showed that the relationship between right foot balance and left foot dollyo chagi kick was 0.721, the relationship between left foot balance and right foot dollyo chagi kick 0.467, leg muscle power relationship with right foot kick ability 0.513, leg muscle power relationship with left foot kick ability 0.748, right foot balance relationship and leg muscle power with left foot dollyo chagi kick 0.727, the relationship between left leg balance and leg muscle power with dollyo chagi kick on the right leg 0.626. These results showed that the relationship between balance and leg muscle power on dollyo chagi kick ability had a significant relationship. The relationship between balance of right foot and leg muscle power with dollyo chagi kick of left leg 0.727, relationship of balance of left leg and leg muscle power with dollyo chagi kick of right leg 0.626. Thus the results showed that the relationship between balance and leg muscle power on dollyo chagi kick ability had a significant relationship.